Caribbean Report 04-03-1999 - The British Broadcasting Corporation; Richards, Ken (anchor, correspondent); Scher, Peter (correspondent); Ransome, Debbie (correspondent); Briceno, Juan Antonio (interviewee); Richardson, Wakefield (correspondent); Holding, Michael (interviewee); Symmonds, Donna (interviewee); Adrien, Peter (interviewee); Lara, Brian (interviewee) (The British Broadcasting Corporation, 1999)
1. Headlines with anchor Ken Richards (00:25) 2. The trade war over bananas between US and the European Union (EU) escalated after US announced procedures for sanctions against the EU. American special trade negotiator Peter Scher comments on the preparatory steps to impose sanctions. EU Trade Commission Sir Leon Brittan discusses the ongoing trade dispute. Debbie Ransome reports on the decision (00:25 - 05:00) 3. Several EU products were affected by punitive US tariff duties. Ken Richards reports on the EU products affected and the negative effect on EU companies (05:01 – 06:39) 4. The developments in the banana trade war is being closely watched by Caribbean banana growers. In Belize, Deputy Prime Minister Juan Antonio Briceño voices his concerns given the importance of the industry to the Caribbean (06:40 - 09:02) 5. The CARICOM intercessional meeting opened in Suriname and one of the key agenda items will be the banana trade war between the US and the European Union (9:03 – 10:29) 6. In Anguilla, voters are casting their ballots in the country’s general elections for sixteen candidates for seven seats. Wakefield Richardson reports on pending polling results, voter turnout and problems experienced during the voting process (10:30 - 11:55) 7. Michael Holding discusses West Indies competitive chances against Australia. The first test starts in Port of Spain, Trinidad and Tobago. Cricket commentator Donna Symonds comments on Captain Brian Lara’s ability to lead and motivate the team to win the series against the world champion Australia. Saint Lucia Peter Adrien, cricket researcher, speaks on the selection of new players to the team. Captain Brian Lara responds to reporters questions on the team performance (11:56 - 15:21)